2008
DOI: 10.1111/j.1939-1676.2008.0105.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Benazepril on Survival and Cardiac Events in Dogs with Asymptomatic Mitral Valve Disease: A Retrospective Study of 141 Cases

Abstract: BNZ had beneficial effects in asymptomatic dogs other than CKC and KC affected by MVD with moderate-to-severe MR. Breed distribution should be taken into account for interpretation of clinical trials performed in dogs with cardiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 43 publications
0
30
1
1
Order By: Relevance
“…Plasma NT‐proBNP measurement may therefore be used to complement ultrasound‐imaging techniques and help stratify and monitor MR severity during the asymptomatic phase of canine MVD. Detecting dogs with the most severe MR or that are at a higher risk of decompensation could have a therapeutic impact 5,6 that needs to be accurately assessed in further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma NT‐proBNP measurement may therefore be used to complement ultrasound‐imaging techniques and help stratify and monitor MR severity during the asymptomatic phase of canine MVD. Detecting dogs with the most severe MR or that are at a higher risk of decompensation could have a therapeutic impact 5,6 that needs to be accurately assessed in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Splitting subgroup 1‐a into dogs with moderate to severe MR and those with mild MR was a posthoc comparison, which is another limitation of the present study. Lastly, more than 40% of dogs with asymptomatic MVD were receiving one or more treatments at the time of diagnosis, including at least an angiotensin‐converting enzyme inhibitor, which could have influenced both the MVD outcome 5,6 and plasma NT‐proBNP concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion by Kittleson et al that all 3 published studies found that “ACEIs do not prolong the time to onset of heart failure in any breed with MVD” is incorrect, as the 16 authors of Vetproof concluded that “results suggest that enalapril modestly delays the onset of CHF in dogs with moderate to severe mitral regurgitation (MR).” 1 Moreover, the implication that, in our study, we tried to hide results is unfounded: the fact that no significant differences in the time of onset of CHF were found between the ACEI and untreated groups is clearly stated on page 909 2 …”
Section: Conclusion On Aceis In Stage 1 Mitral Valve Disease (Mvd)mentioning
confidence: 81%
“…We have the same concerns we published in our earlier letter to the editor about Pouchelon and colleagues' study, and wish to refute certain statements made in their letter 1–3 . Our point was not to indict retrospective studies per se.…”
mentioning
confidence: 76%